(The Effect Of Soccer Invasion Game On Students' Motoric Skills At State Elementary School 066045 Grade VI Medan) - Hutahean, Alridoi Mulia (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to determine the effect of soccer invasion games on the motor skills of sixth-grade students at UPT SD Negeri 066045 Medan in the 2024/2025 academic year. This research uses a quantitative approach with an experimental method of One Group Pretest-Posttest Design. The sample consisted of 20 students selected using total sampling. Data collection was conducted through observation of students' motor skills in dribbling, passing, and shooting. The results showed an increase in the average score from the pre-test (69.05) to the post-test (80.10). Based on the t-test analysis, the significance value (Sig. 2-tailed) was 0.000 < 0.05, indicating that there was a significant effect of soccer invasion games on improving students' motor skills. Thus, soccer invasion games can be used as an alternative learning method to enhance the motor skills of elementary school students..